Complete chloroplast genome sequences of important oilseed crop Sesamum indicum L. - Dong-Keun Yi (Public Library of Science (PLoS), 2012)
Sesamum indicum is an important crop plant species for yielding oil. The complete chloroplast (cp) genome of S. indicum (GenBank acc no. JN637766) is 153,324 bp in length, and has a pair of inverted repeat (IR) regions consisting of 25,141 bp each. The lengths of the large single copy (LSC) and the small single copy (SSC) regions are 85,170 bp and 17,872 bp, respectively. Comparative cp DNA sequence analyses of S. indicum with other cp genomes reveal that the genome structure, gene order, gene and intron contents, AT contents, codon usage, and transcription units are similar to the typical angiosperm cp genomes. Nucleotide diversity of the IR region between Sesamum and three other cp genomes is much lower than that of the LSC and SSC regions in both the coding region and noncoding region. As a summary, the regional constraints strongly affect the sequence evolution of the cp genomes, while the functional constraints weakly affect the sequence evolution of cp genomes. Five short inversions associated with short palindromic sequences that form step-loop structures were observed in the chloroplast genome of S. indicum. Twenty-eight different simple sequence repeat loci have been detected in the chloroplast genome of S. indicum. Almost all of the SSR loci were composed of A or T, so this may also contribute to the A-T richness of the cp genome of S. indicum. Seven large repeated loci in the chloroplast genome of S. indicum were also identified and these loci are useful to developing S. indicum-specific cp genome vectors. The complete cp DNA sequences of S. indicum reported in this paper are prerequisite to modifying this important oilseed crop by cp genetic engineering techniques.